Versatile printed microheaters to enable low-power thermal control in paper diagnostics. Issue 1 (15th November 2019) - Byers, Kristin M.; Lin, Li-Kai; Moehling, Taylor J.; Stanciu, Lia; Linnes, Jacqueline C.
Abstract : Reusable, low-power, low-cost, printed microheaters developed for practical use in in-field and point-of-care diagnostics. Abstract : As the capabilities of low-resource field testing have begun to expand to incorporate more complex diagnostic technologies, many of these devices remain tethered to large heaters requiring relatively high-power inputs. Highly efficient microheaters would enable miniaturization of devices for more economic and effective heating with high temperatures and sustained incubation. This work reports the development and application of resistive microheaters printed with nanosilver ink for improved methods of automated sample heating in paper-based point-of-care (POC) and in-field diagnostics. Resistance is easily predicted, and shapes can be altered to fit space and heat-transfer needs, sustained and discrete heating of precise regions are possible. Here, we demonstrate both isothermal nucleic acid amplification at 65 °C and bacterial culture at 37 ° C using our microheaters. Printed nanosilver microheaters are easily integrated into reactions that require low-power battery heating, can sustain heating for 16-hour incubations, and cost between 0.17 and 0.58 US dollars each. Further, the microheaters are reusable, stable over 6 months, and can be wetted without degradation or reduction in conductivity. These versatile printed microheaters enable thermal control for a variety of low power heating applications.